Investigations into Marketing Communication Tools on Bank Marketing Strategy in Ghana - Tandoh, Isaac; Boateng, Frank (IJRAR- International Journal of Research and Analytical Reviews, 2019)
This study sought to examine the various marketing communication tools and strategies employed by selected financial institutions in Kumasi in marketing their products and services. The primary research tool used for this study was questionnaires and observations. Statistical tools like mean and standard deviation were used. Table and graphs were used to simplify the analysis. Questionnaires were administered to management staff and customers of the selected banks who served as respondents for the study. The study revealed that, the most effective marketing communication tool for the banks tool was personal selling. Evidently Personal selling (PS) proved to be the marketing communication tool with the strongest correlation (0.856) with the performance, followed by public relation and direct marketing ((PR)) which had a correlation coefficient value of (0.775).Nevertheless, the study established that, marketing tools such as personal selling, public relations, direct market, and advertisements were all important tools for communicating to the general public but personal selling gives the chance for the company representative to explain in words of convincing to the customer and opportunity to answer the queries of the customer. On the basis of the findings, it was recommended that adequate training be given to the marketing managers and proper implementation and evaluation schemes be put in place to measure the effectiveness of communication strategies. Additionally, well trained staff and professionals were needed to champion this strategic function of management.
Research Article
Keywords: Investigations, Marketing Communication Tools, Bank Marketing Strategy, Ghana